Implementasi Weighted Moving Average dalam Sistem Informasi Peramalan Stok Material Finishing di Industri Mebel Wahyu Furniture - A. Faiq Abror; Sofia Ulfah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This research develops a Finishing Material Stock Forecasting Information System using the Weighted Moving Average (WMA) method to address inventory management challenges at Wahyu Furniture Industry. The current production process, particularly in the finishing stage, faces difficulties in material prediction due to manual Excel-based recording without proper forecasting tools, potentially causing material ordering inaccuracies. Adopting the Rapid Application Development (RAD) approach, the website and MySQL database-based system was developed through three iterative phases: requirements planning, system design, and implementation. Analysis of 100 historical data points over Year 2024 revealed highest accuracy (MAPE 16.705%) at n=5 parameter. Validation by 5 respondents demonstrated 76.5% feasibility score, proving the system's effectiveness in optimizing finishing material stock and resolving surplus/shortage problems.